Security auditing of web security vulnerabilities using program analysis : mobile application recommendation - Yong, Chen Feng (2019)
Security Auditing of Web Security Vulnerabilities using Program Analysis - The rate of evolution in the world of technology and the internet is increasing at an overwhelming rate in recent years. Today, people rely on the internet for various reasons. The main usage of the internet is to help people to connect and communicate with one another in the different sector of the world through the means of web applications [1]. As technology and the internet evolve, cybersecurity concerns have also been on the rise as hacker probe into the vulnerabilities due to the fast-evolving technology.